Nonpecuniary Rewards in the Workplace: Demand Estimates Using Quasi-Market Data - Cavalluzzo, Linda C. (The Review of Economics and Statistics, 1991)
Lack of explicit markets and associated data have impeded measurement of nonpecuniary rewards in the workplace. Most of the published literature employs hedonic models that permit estimation of market-clearing prices, but do not allow for identification of demand schedules. In an alternative approach, used successfully by environmental economists, the author develops quasi-market data and uses it to estimate demand for the nonpecuniary rewards associated with leadership. In addition to price responsiveness, individuals exhibit tastes for the amenities of leadership that differ substantially, and in expected directions, with their personal and professional characteristics. Copyright 1991 by MIT Press.